Experience of metal deposits combined development for South African enterprises - Golik, V.; Komashchenko, V.; Morkun, V.; Burdzieva, O. (Розробка родовищ, 2017)
Purpose. To solve technological and ecological problems of South Africa and other countries using the experience of Russian, Kazakh and Ukrainian miners in mining metals by the combination of traditional and new technologies. The ultimate aim of environmental protection concept is waste-free minerals mining with full utilization of the components produced from mined raw materials. Findings. A brief review of the state of metal production in the world is presented. The environmental trends of mining engineering humanization in technologically advanced countries are defined. The experience of underground leaching of uranium is described. The results of pioneer experiments on the extraction of metals using combined mechanic and chemical treatment in the disintegrator are provided. Economic-mathematical models have been developed in order to determine efficiency of using combined technologies and simulate results of metal extraction. Мета. Вирішення технологічних і екологічних проблем Південної Африки та інших країн із використанням досвіду російських, казахстанських та українських шахтарів при видобуванні металів, що поєднують традиційні й нові технології. Кінцевою метою концепції захисту навколишнього середовища є безвідходний видобуток корисних копалин з повним використанням компонентів, отриманих з видобутої сировини. Результати. Дана коротка довідка про стан виробництва металів у світі. Охарактеризовані природоохоронні тенденції гуманізації гірничої справи в технологічно розвинених країнах. Описано досвід підземного вилуговування урану. Наведено результати піонерних експериментів із вилучення металів комбінованою механохімічною обробкою у дезинтеграторі. Сформульовано економіко-математичні моделі визначення ефективності використання комбінованої технології та моделювання результатів отримання металів. Цель. Решение технологических и экологических проблем Южной Африки и других стран с использованием опыта российских, казахстанских и украинских шахтеров при добыче металлов, сочетающих традиционные и новые технологии. Конечной целью концепции защиты окружающей среды является безотходная добыча полезных ископаемых с полным использованием компонентов, полученных из добытого сырья. Результаты. Дана краткая справка о состоянии производства металлов в мире. Охарактеризованы природоохранные тенденции гуманизации горного дела в технологически развитых странах. Описан опыт подземного выщелачивания урана. Приведены результаты пионерных экспериментов по извлечению металлов комбинированной механохимической обработкой в дезинтеграторе. Сформулированы экономико-математические модели определения эффективности использования комбинированной технологии и моделирование результатов получения металлов.